Falling Less in Kansas: Development of a Fall Risk Reduction Toolkit - Teresa S. Radebaugh; Candace A. Bahner; Deborah Ballard-Reisch; Michael Epp; LaDonna S. Hale; Rich Hanley; Karen Kendrick; Michael E. Rogers; Nicole L. Rogers (Journal of Aging Research)
Falls are a serious health risk for older adults. But for those living in rural and frontier areas of the USA, the risks are higher because of limited access to health care providers and resources. This study employed a community-based participatory research approach to develop a fall prevention toolkit to be used by residents of rural and frontier areas without the assistance of health care providers. Qualitative data were gathered from both key informant interviews and focus groups with a broad range of participants. Data analysis revealed that to be effective and accepted, the toolkit should be not only evidence based but also practical, low-cost, self-explanatory, and usable without the assistance of a health care provider. Materials must be engaging, visually interesting, empowering, sensitive to reading level, and appropriate for low-vision users. These findings should be useful to other researchers developing education and awareness materials for older adults in rural areas.